HISTORY OF MAKTAB AL-ISLAMIYAH TAPANULI - Asari, Hasan; Tanjung, Muaz (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2019)
Maktab al-Islamiyah Tapanuli is the earliest formal Islamic institution in Medan, North Sumatra. It seems that this institution has not received the attention it deserves, especially for its pioneering position. This might not be soo surprising, because, in general, Islamic education in North Sumatra has not drawn the attention of researchers as much as that of neighbouring Aceh or Minangkabau. This article is an attempt to present a primary source on the topic, i.e. a short treatise entitled History of Maktab al-Islamiyah Tapanuli. This book is an academic heritage left behind by `alim-historian of Medan, Syekh Abubakar Ya?qub (d. 1982). Here, it is posthumously published so that it can be used to enhance our understanding of the history of Islamic education in North Sumatra. Although the work itself is short but it is very important, since it contains first-hand information put together by a man who took part in the series of event he recorded. This work provides primary data and notes that should be of most importance for researchers.